DETERMINATION OF LYCOPENE CONTENT IN CULTIVARS OF SOLANUM LICOPERSICUM GROWN IN GREENHOUSE CONDITIONS - Miljković, Vojkan (Acta medicae Medianae, 2022)
Lycopene is carotenoid, the pigment responsible for color of ripe tomato. The aim of this study was to determinate and compare lycopene content in fresh tomato grown under greenhouse conditions in Serbia (cultivar Hector-F1), North Macedonia (cultivar Hamzali-F1), Greece (cultivar Optima-F1) and Turkey (cultivar Benetar-F1). For this purpose, spectrophotometric method was used. The highest lycopene content is found to be in tomato grown in Serbia tomato, followed with Turkey, Greece and North Macedonia with values per 1 kg of fresh fruit 81.53 mg, 76.33 mg, 27.92 mg and 13.49 mg respectively. The results showed that fresh tomato is good source of lycopene and it should be consumed in everyday meals.